New Strategies for Social Innovation : Market-Based Approaches for Assisting the Poor. - Anderson, Steven G. (Columbia University Press, 2014)
Market-based development strategies designed to help the world's poor receive significant support from advocates, academics, governments, and the media, yet frequently the perceived success of these programs rests on carefully selected examples and one-sided, enthusiastic accounts. In practice, these approaches are often poorly defined and executed, with little balanced, comparative analysis of their true strengths and weaknesses. This book is the first to assess emerging market-based social change approaches comparatively, focusing specifically on social entrepreneurship, corporate soci.